2017
DOI: 10.1111/rda.13109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of perivascular and stromal mesenchymal stem/progenitor cells in porcine endometrium

Abstract: Mammalian uterus contains a population of mesenchymal stem/progenitor cells that likely contribute to endometrial regeneration during each reproductive cycle. In human and mouse, they reside in perivascular, epithelial and stromal compartments of the endometrial functionalis and basalis. Here, we aimed to identify tissue resident cells expressing mesenchymal stem cell markers CD29, CD44, CD90, CD105, CD140b and CD146 in the porcine endometrium. We used single immunofluorescence and Western blotting. Each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Endometrial stem cells (EnSCs) are identified in both the functional and basal layer of regenerative human endometrium [15,16], which can be used for the reconstruction of the human uterus and other organs [17,18]. They can be easily obtained from menstrual blood shedding without invasive surgical intervention or hospitalization, and the isolation is free of ethical concerns [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial stem cells (EnSCs) are identified in both the functional and basal layer of regenerative human endometrium [15,16], which can be used for the reconstruction of the human uterus and other organs [17,18]. They can be easily obtained from menstrual blood shedding without invasive surgical intervention or hospitalization, and the isolation is free of ethical concerns [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…34 These stem cells make great contribution to the regeneration of endometrium after menstruation and injury to uterus. 34,35 This leads us to think about whether the effect of E 2 -HP hydrogel in endometrial cell regeneration is associated with the recruitment of stem cells in endometrium. Our future studies will focus on its role in the recruitment of stem cells, the improvement of local inflammation and specific mechanism underlying these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many recent studies have demonstrated that there are small populations of endometrial stem cells existing in the endometrium . These stem cells make great contribution to the regeneration of endometrium after menstruation and injury to uterus . This leads us to think about whether the effect of E 2 ‐HP hydrogel in endometrial cell regeneration is associated with the recruitment of stem cells in endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-4A is a transcription factor in the nucleus that maintains the differential potency of embryonic and adult stem cells, whereas cytoplasmic expressed OCT-4B is not involved in stem cell regulation [ 31 ]. The cytoplasmic localization of OCT-4 detected in MenSCs therefore led to doubts about the pluripotency of MenSCs [ 6 , 28 , 32 ]. However, a recent investigation of mouse endometrium revealed the presence of very small embryonic-like stem cells (VSELs), which expressed nuclear transcripts of OCT-4, accounting for approximately 0.069% of the total endometrial cells.…”
Section: Cell Markers Of Menscsmentioning
confidence: 99%